2014
DOI: 10.1136/medethics-2013-101930
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of the empirical evidence on public attitudes on brain death and vital organ transplantation: the need for better data to inform policy

Abstract: Vital organ transplantation is premised on 'the dead donor rule': donors must be declared dead according to medical and legal criteria prior to donation. However, it is controversial whether individuals diagnosed as 'brain dead' are really dead in accordance with the established biological conception of death-the irreversible cessation of the functioning of the organism as a whole. A basic understanding of brain death is also relevant for giving valid, informed consent to serve as an organ donor. There is ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 49 publications
3
55
0
2
Order By: Relevance
“…It is well-known that in both the United States and abroad, public awareness of the irreversibility of DNC is poor. 19 One would hope that medical students have a strong understanding of DNC, but a brief test showed that their level of understanding of this topic was low. 20 These results were mirrored in a test on DNC given to practicing neurologists, who were able to correctly answer only 54% of questions.…”
Section: Solo Practice 21 20mentioning
confidence: 99%
“…It is well-known that in both the United States and abroad, public awareness of the irreversibility of DNC is poor. 19 One would hope that medical students have a strong understanding of DNC, but a brief test showed that their level of understanding of this topic was low. 20 These results were mirrored in a test on DNC given to practicing neurologists, who were able to correctly answer only 54% of questions.…”
Section: Solo Practice 21 20mentioning
confidence: 99%
“…It was found that higher knowledge about OD will help in creating positive attitude (Shah et al, ), and the value perceived by an individual can increase the attitude towards donation (Shim & Eastlick, ). Value perceived by the individual means the “value perceived by the donor in the act of donation.” If the donor perceives high value, then he/she is likely to have positive attitude towards OD.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given the lack of information available on OPO websites, 87 and the use of mass media campaigns as advertisements rather than information sources, 88 it is unsurprising that Mrs Smith alleged that her son, like much of the general public, 86 did not have a reasonable understanding of the circumstances of organ procurement to allow an informed choice, particularly when he registered as an organ donor by checking a box at a motor vehicle agency.…”
Section: Elijah Smithmentioning
confidence: 99%
“…51 There is substantial confusion among the public about both brain death and organ procurement. In a recent review of the international literature on public beliefs and attitudes, Shah et al 86 found misunderstanding about basic clinical facts about brain death, about the legal status of brain death, and about the process of organ procurement, particularly that it takes place while the donor remains on the ventilator with a beating heart. Furthermore, a quantitative study of the websites of organ procurement organizations and internet consent forms for organ donation in the USA revealed a nearly complete lack of information that was recommended for informed consent for organ donation by the US Department of Health and Human Services Advisory Committee on Organ Transplantations.…”
mentioning
confidence: 99%